Investigation on Interaction of Buflomedil Hydrochloride with Trypsin: A Spectroscopic Analysis - Li, Xiaoling; Zhang, Xiaoping; Wang, Li; Gao, Xiaoyan; Zhao, Wujie; Zi, Yanqin (Asian Journal of Chemistry, 2012)
The interaction between buflomedil hydrochloride and trypsin has been studied through fluorescence spectroscopy and UV/VIS spectrophotometry. With the addition of buflomedil hydrochloride, the fluorescence emission intensity of trypsin was quenched. The number of binding sites and the binding constants were measured by the fluorescence quenching method. Thermodynamic parameters DH, DG and DS at three temperatures (293 K, 300 K, 310 K) were calculated. The force acting between buflomedil hydrochloride and trypsin was mainly a hydrophobic interaction. The binding distance between the donor (trypsin) and acceptor (buflomedil hydrochloride) was 0.862 nm according to Förster's non-radiational energy transfer theory.